Genomics of disease - Gustafson, J. P. (Springer, 2017)
The title will develop from the 24th Stadler symposium. It will explore the general theme "GENOME EXPLOITATION: Data Mining the Genomes." The idea behind the theme is to discuss and illustrate how scientists are going to characterize and make use of the massive amount of information being accumulated about plant and animal genomes. The book will present a state-of-the-art picture on mining the Genome databases. This will be one of the few times that researchers in both plants and animals will be working together to create a seminal data resource.